Introduction to Philosophy Logic - Martin, Ben; Hendricks, Christina (Open textbook library., 2020)
Introduction to Philosophy: Logic provides students with the concepts and skills necessary to identify and evaluate arguments effectively. The chapters, all written by experts in the field, provide an overview of what arguments are, the different types of arguments one can expect to encounter in both philosophy and everyday life, and how to recognise common argumentative mistakes.